Voltage Dependent Anion Channel Is Redistributed during Japanese Encephalitis Virus Infection of Insect Cells. (10th July 2014) - Fongsaran, Chanida; Phaonakrop, Narumon; Roytrakul, Sittiruk; Thepparit, Chutima; Kuadkitkan, Atichat; Smith, Duncan R.
Abstract : Despite the availability of an effective vaccine, Japanese encephalitis remains a significant cause of morbidity and mortality in many parts of Asia. Japanese encephalitis is caused by the Japanese encephalitis virus (JEV), a mosquito transmitted flavivirus. Many of the details of the virus replication cycle in mosquito cells remain unknown. This study sought to determine whether GRP78, a well-characterized flavivirus E protein interacting protein, interacted with JEV E protein in insect cells, and whether this interaction was mediated at the cell surface. GRP78 was shown to interact with JEV E protein by coimmunoprecipitation, and was additionally shown to interact with voltage dependent anion protein (VDAC) through the same methodology. Antibody inhibition experiments showed that neither GRP78 nor VDAC played a role in JEV internalization to insect cells. Interestingly, VDAC was shown to be significantly relocalized in response to JEV infection, and significant levels of colocalization between VDAC and GRP78 and VDAC and ribosomal L28 protein were seen in JEV infected but not uninfected cells. This is the first report of relocalization of VDAC in response to JEV infection and suggests that this may be a part of the JEV replication strategy in insect cells.